1994
DOI: 10.2134/agronj1994.00021962008600040013x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Kura Clover to Sheep Grazing and Clipping: I. Yield and Forage Quality

Abstract: Few perennial legumes have dependable long‐term productivity under grazing in the northern USA. Our objective was to determine the effects of frequent clipping and sheep(Ovis spp.) grazing on forage yield and quality of kura clover (Trifolium ambiguum. Bieb.), a rhizomatous perennial legume. Clipping and grazing trials were initiated on a 5‐yr‐old stand of ‘Rhizo’ kura clover on a Waukegan silt loam and conducted for 3 yr. Total season yield (mean of 8.6 Mg ha‐1) was unaffected by clipping frequency until the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 12 publications
6
49
2
Order By: Relevance
“…Indeed it appeared that the plots of Monaro were more closely grazed than those of the other species. Caucasian clover can tolerate frequent, close defoliation while maintaining stand density under set-stocked conditions (Peterson et al 1994). The absence of Monaro in the germinable seed bank is an indication that it persisted because of vegetative reproduction and not because of seedling regeneration.…”
Section: High Phosphatementioning
confidence: 99%
See 3 more Smart Citations
“…Indeed it appeared that the plots of Monaro were more closely grazed than those of the other species. Caucasian clover can tolerate frequent, close defoliation while maintaining stand density under set-stocked conditions (Peterson et al 1994). The absence of Monaro in the germinable seed bank is an indication that it persisted because of vegetative reproduction and not because of seedling regeneration.…”
Section: High Phosphatementioning
confidence: 99%
“…Although some modelling of the potential distribution of this legume has been attempted , there remains significant doubt as to the true range of its adaptation as few trials outside high altitude areas (> 800 m) have been reported. Recent studies have focussed on production, persistence, and quality under various cutting or grazing regimes (Allinson et al 1985;Sheaffer & Marten 1991;Peterson et al 1994). These studies have shown that Caucasian clover is best grazed over long rotations to maintain it as the dominant component and to maintain production overall.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with other temperate forage legumes, the seasonal yield distribution of Kura clover is uneven, producing most of its DM in the spring with forage accumulation and yields decreasing throughout the season (Peterson et al 1994a;Seguin et al 2000). Thus, conservation of excess forage is desirable.…”
mentioning
confidence: 99%